Increased air temperature during repeated-sprint training in hypoxia amplifies changes in muscle oxygenation without decreasing cycling performance - Dennis, M. C.; Goods, P. M. R.; Binnie, M. J.; Girard, O.; Wallman, K. E.; Dawson, B.; Billaut, F.; Peeling, P. (European Journal of Sport Science, 2023)
The present study aims to investigate the acute performance and physiological responses, with specific reference to muscle oxygenation, to ambient air temperature manipulation during repeated-sprint training in hypoxia (RSH). Thirteen male team-sport players completed one familiarisation and three experimental sessions at a simulated altitude of ~3000 m (FIO2 0.144). Air temperatures utilised across the three experimental sessions were: 20°C, 35°C and 40°C (all 50% relative humidity). Participants performed 3 × 5 × 10-s maximal cycle sprints, with 20-s passive recovery between sprints, and 5 min active recovery between sets. There were no differences between conditions for cycling peak power, mean power, and total work (p>0.05). Peak core temperature (Tc) was not different between conditions (38.11±0.36°C). Vastus lateralis muscle deoxygenation during exercise and reoxygenation during recovery was of greater magnitude in 35°C and 40°C than 20°C (p<0.001 for all). There was no condition × time interaction for Tc, skin temperature, pulse oxygen saturation, heart rate, rating of perceived exertion and thermal sensation (P>0.05). Exercise-induced increases in blood lactate concentration were higher in 35°C and 40°C than 20°C (p=0.010 and p=0.001, respectively). Integrating ambient temperatures up to 40°C into a typical RSH session had no detrimental effect on performance. Additionally, the augmented muscle oxygenation changes experienced during exercise and recovery in temperatures >35°C may indicate that the potency of RSH training is increased with additional heat. However, alterations to the training session may be required to generate a sufficient rise in Tc for heat training purposes.